Students Resilience Through Reciting Hizib Sirrul Mashun as a Living Qur'an Tradition in Pondok Pesantren Al-Hidayah Purwokerto - Budiyono, Alief (IBDA` : Jurnal Kajian Islam dan Budaya, 2022)
This article examines the reciting Hizb Sirrul Mashun as a living Qur'an tradition at Pondok Pesantren Al-Hidayah, Purwokerto. It is field research with a descriptive-qualitative method, and the researcher gets research data through in-depth interviews, observations, and studies of related documents. He uses data reduction, display data, and conclusions in analyzing data. The results are, First, students (Santri) recite Hizb Sirrul Mashun during Coronavirus disease (COVID-19) pandemic whose goal is a dynamic process of positive adaptation to adversity, Second, fasting for seven consecutive days—for students who are just practicing. During the implementation process, if the students fail both in reciting the Hizb or the fast, They repeat it from the beginning. The senior student leads the reciting at the An-Nur Karangsuci Mosque. Practically, the students recite Hizb Sirrul Mashun at the Pondok Pesantren Al-Hidayah Karangsuci Purwokerto after the congregational evening prayer on Friday night. Third, based on the Sociological theory of Karl Mannheim, the meaning contained in the reciting of Hizb Sirrul Mashun includes three aspects, namely objective, expressive, and documentary. The objective meaning emphasizes that the reciting of Hizb Sirrul Mashun is also strongly influenced by the social support implemented in Kyai's words. One of the factors supporting resilience is social support. The expressive meaning from the students (Santri) emphasizes that other factors influence the formation of resilience, namely religiosity and spirituality.